2009
DOI: 10.2174/1652803400901010052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nearby Buildings on Electromagnetic Fields from Lightning

Abstract: Abstract:We present a discussion on the effect of nearby buildings on the electric and magnetic fields radiated by lightning. Electric and magnetic fields radiated from distant natural lightning have been measured simultaneously on the roof of a building (the Power Systems Laboratory of the Swiss Federal Institute of Technology, Lausanne, Switzerland) and on the ground at different distances away from it. The results suggest that the measured electric field on the roof of the 9-m tall building is enhanced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It is known that the building on top of which the measuring sensors are located can affect the measured signals (Baba & Rakov, 2007b;Mosaddeghi et al, 2009). For example, Baba and Rakov (2007b) have shown that a 20m tall building can result in an enhancement factor of 1.5.…”
Section: Lightning Current and Electric Field Measuring Systemsmentioning
confidence: 99%
“…It is known that the building on top of which the measuring sensors are located can affect the measured signals (Baba & Rakov, 2007b;Mosaddeghi et al, 2009). For example, Baba and Rakov (2007b) have shown that a 20m tall building can result in an enhancement factor of 1.5.…”
Section: Lightning Current and Electric Field Measuring Systemsmentioning
confidence: 99%
“…: Finally, it is well known that the presence of the building on which the field sensors are located might affect the measured waveform (e.g., [37] and [38]). In particular, the electric field measured on the roof of a building might experience an enhancement that depends on several factors related to the building (shape, material, presence of conducting beams, etc.)…”
Section: ) Presence Of the Building On Which The Field Sensor Ismentioning
confidence: 99%
“…As can be seen in Figures 6a and 6b, the vertical component of the electric field waveforms predicted by the proposed model is more consistent with the measurement data from the point of view of the field's higher peak, trend and late time values. However, both extensions of the AT model have still a high difference in level with the measured values, that is significantly larger than the simulation predictions, this effect can be ascribed to the building enhancement effect that is discussed by Pavanello et al [2007a, 2007b], Baba and Rakov [2007b], and Mosaddeghi et al [2009]. The main feature of the proposed model is demonstrated in the case of far distance (Figure 6c) where, as opposed to the ATIL‐F model, a zero crossing time of 42.85 μ s in distance of 50 km is reproduced in the predicted vertical electric and the azimuthal magnetic field waveforms.…”
Section: Simulation Resultsmentioning
confidence: 78%